Constructions of Dense Lattices of Full Diversity - Andrade, A. A. [UNESP]; Ferrari, A. J. [UNESP]; Interlando, J. C.; Araujo, R.r. (Sociedade Brasileira de Matemática Aplicada e Computacional, 2020)
A lattice construction using â„¤-submodules of rings of integers of number fields is presented. The construction yields rotated versions of the laminated lattices Î›n for n = 2, 3, 4, 5, 6, which are the densest lattices in their respective dimensions. The sphere packing density of a lattice is a function of its packing radius, which in turn can be directly calculated from the minimum squared Euclidean norm of the lattice. Norms in a lattice that is realized by a totally real number field can be calculated by the trace form of the field restricted to its ring of integers. Thus, in the present work, we also present the trace form of the maximal real subfield of a cyclotomic field. Our focus is on totally real number fields since their associated lattices have full diversity. Along with high packing density, the full diversity feature is desirable in lattices that are used for signal transmission over both Gaussian and Rayleigh fading channels.

Uma construÃ§Ã£o de reticulados usando â„¤ submÃ³dulos de anÃ©is de inteiros de corpos de nÃºmeros Ã© apresentada. A construÃ§Ã£o produz versÃµes rotacionadas dos reticulados laminados Î›n para n = 2, 3, 4, 5, 6, que sÃ£o os reticulados mais densos nessas dimensÃµes. A densidade de empacotamento esfÃ©rico de um reticulado Ã© uma funÃ§Ã£o do seu raio de empacotamento, o qual por sua vez pode ser diretamente calculado a partir da norma quadrada mÃnima do reticulado. Normas em um reticulado realizado por um corpo de nÃºmeros totalmente real podem ser calculadas pela forma traÃ§o do corpo restrita ao seu anel de inteiros. Portanto, no presente trabalho, apresentamos tambÃ©m a forma traÃ§o do subcorpo real maximal de um corpo ciclotÃ´mico. Nosso foco Ã© em corpos de nÃºmeros totalmente reais pois os reticulados associados a eles possuem diversidade mÃ¡xima. Juntamente com a densidade de empacotamento, a caracterÃstica de diversidade mÃ¡xima Ã© desejÃ¡vel em reticulados que sÃ£o usados para transmissÃ£o de sinais que percorrem os canais gaussiano e de desvanecimento Rayleigh.
Keywords: sphere packings; algebraic lattices; number fields; cyclotomic fields; empacotamento de esferas; reticulados algébricos; corpos de números; corpos ciclotômicos